REHABILITATION OF DRUGS ABUSE VICTIMS THROUGH ISLAMIC PSYCHOTHERAPY APPROACH AT IPWL D’WIN FOUNDATION BANGKA BELITUNG - Armika, Armika; Dewi, Indah Kusuma; Zayadi, Zayadi (Psychosophia: Journal of Psychology, Religion, and Humanity, 2023)
Islamic psychotherapy is an attempt to help heal and treat clients through the emotional and spiritual aspects of a person in an Islamic way and does not contradict or conflict with Islamic religious teachings which are based on the guidance of the Qur’an and the Hadith. The purpose of this study is to find out how successful Islamic psychotherapy is for clients in drug abuse rehabilitation at IPWL D’WIN Foundation Bangka Belitung. Based on the results of the study, it can be concluded that the success of Islamic psychotherapy for clients in IPWL D’WIN Foundation rehabilitation is carried out through providing deepening, appreciation, and religious practice that can grow and increase the spiritual strength of drug addict clients so that they can recover and be healthy again and can minimize re-engagement in drug abuse.